Influencing the effectiveness of post-stroke motor rehabilitation factors - D. V. Zaharov; V. A. Mihailov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
The issues of neurorehabilitation of stroke patients are considered. The importance of the phenomenon of neuroplasticity, which underlies the regenerative processes after brain damage is emphasized. The principles of rehabilitation therapy in stroke patients are considered. Particular attention is paid to the issue of pharmacotherapy through neurotransmitters focused on increasing neuroplasticity and neurogenesis.